Examining the impact of a brief cognitive-behavioral intervention on anxiety sensitivity: Preliminary findings - Jokić-Begić, Nataša (Array, 2011)
Introduction: Anxiety sensitivity (AS) is the fear of anxiety and anxiety-related sensations, based on the belief that such sensations will lead to harmful somatic, psychological, or social consequences. Elevated levels of AS have been considered as a cognitive risk factor for the development and maintenance of various forms of psychopathology, particularly anxiety disorders. As some research suggest that AS mostly arises from a variety of learning experiences that result in acquisition of beliefs about potentially aversive effects of anxiety symptoms, targeting AS may be critical for the prevention and treatment of many psychological disorders. The aim of our study, which is in progress, is to examine the effectiveness of a brief cognitive-behavioral intervention designed to reduce AS and to prospectively evaluate the effects of this intervention on the incidence of various psychological problems during a 12-month follow-up period. The findings of a preliminary research, as a part of this broader study, will be presented. Method: A total of 45 high AS subjects were assigned to one of 3 experimental conditions: a brief cognitive-behavioral intervention aimed at decreasing AS, an education on health control condition, and no-treatment control condition. Each intervention was delivered via computer and was completed in a single session of approximately 45 minutes. Several self-report (Anxiety Sensitivity Index, State-Trait Anxiety Inventory, Self-Assessment Manikin, Clinical Outcomes in Routine Evaluation – Outcome Measure) as well as behavioral measures were administered both at pre- and posttreatment. At posttretament, a semistructured interview on participants' experiences and reflections about intervention was also conducted. Results and discussion: We compared the results within and between groups and conducted a qualitative analysis of experiences of participants. Our preliminary findings are promising, indicating the effectiveness of a brief cognitive-behavioral intervention in the reduction of AS. The practical implications of these findings will be discussed.